Contralateral Orchiopexy at the Time of Urgent Scrotal Exploration—Is It Safe? A Propensity Score Matched Analysis from the TORSAFUF Cohort. Issue 6 (16th December 2021) - Duquesne, Igor; Pinar, Ugo; Dang, Van Thi; Mauger de Varennes, Anne; Benali, Nadia Ali; Berchiche, William; Margue, Gaelle; Gaillard, Charles; Bardet, Florian; Hulin, Maud; Manuguerra, Anthony; Plassais, Caroline; et al.
Abstract : Purpose: We evaluate the safety of immediate contralateral orchiopexy (ICLO) at the time of scrotal exploration for testicular torsion suspicion. Materials and Methods: Patient data were retrieved from the TORSAFUF cohort project, which is a multicenter national study conducted at 14 academic French hospitals between 2005 and 2019. Each patient who underwent surgical exploration for testicular torsion suspicion was included. The primary study outcome was the safety of ICLO compared to ipsilateral scrotal exploration alone. The primary outcome of interest was the complication rate within 90 days of surgery. The end point was planned before data collection. Results: Overall, 2, 775 patients were included, of whom 1, 554 (56%) underwent ICLO. After propensity score matching and multivariable analysis, ICLO was associated with a higher complication rate (OR 1.51, 95% CI 1.1–2.1, p=0.01), especially a higher rate of hematoma (OR 2.9, 95% CI 1.3–6.6, p=0.01), and delayed wound healing (OR 3.0, 95% CI 1.8–5.2, p <0.001). Conclusions: At the time of scrotal exploration for acute scrotum, ICLO was associated with an increased postoperative complication rate, with a particular increase in hematoma, and delayed wound healing. ICLO should not be performed systematically.